2018
DOI: 10.1002/stem.2856
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Endothelial Progenitor Cell-Derived Extracellular Mitochondria in Brain Endothelium

Abstract: Endothelial progenitor cells (EPCs) have been pursued as a potential cellular therapy for stroke and central nervous system injury. However, their underlying mechanisms remain to be fully defined. Recent experimental studies suggest that mitochondria may be released and transferred between cells. In this proof-of-concept study, we asked whether beneficial effects of EPCs may partly involve a mitochondrial phenomenon as well. First, EPC-derived conditioned medium was collected and divided into supernatant and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 33 publications
6
117
1
Order By: Relevance
“…123 Brain endothelial cells that endocytose exMTs from endothelial progenitor cells are protected against oxygen-glucose deprivation-induced injury. 124 Macrophages that endocytose exMTs released from mesenchymal stem cells are transformed into highly phagocytic and anti-inflammatory macrophages. 125,126 Bone marrow derived stromal cells transfer mitochondria into pulmonary alveoli to increase ATP production and protect mice against lipopolysaccharide-induced acute lung injury.…”
Section: Extracellular Mitochondria Disrupt Endothelial Integritymentioning
confidence: 99%
“…123 Brain endothelial cells that endocytose exMTs from endothelial progenitor cells are protected against oxygen-glucose deprivation-induced injury. 124 Macrophages that endocytose exMTs released from mesenchymal stem cells are transformed into highly phagocytic and anti-inflammatory macrophages. 125,126 Bone marrow derived stromal cells transfer mitochondria into pulmonary alveoli to increase ATP production and protect mice against lipopolysaccharide-induced acute lung injury.…”
Section: Extracellular Mitochondria Disrupt Endothelial Integritymentioning
confidence: 99%
“…Exosomes are small membrane vesicles that mediate intercellular signal transduction [6]. Previous studies have shown that EPC-derived exosomes can promote angiogenesis and reduce cardiomyocyte hypertrophy and apoptosis [7][8][9]. Furthermore, exosomes had been shown to carry different nucleic acids, including microRNAs (miRNAs), which are acquired by recipient cells to regulate their own fate [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, cells can also release intact mitochondria which retain functional properties [19,20,53,56,57,60]. The transfer of healthy mitochondria has been demonstrated in different tissues and organs, where its main role is to maintain local homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, astrocytes provide healthy mitochondria to damaged neurons to restore normal OXPHOS both in vitro and in vivo [20,53]. Similarly, endothelial progenitor cells support brain endothelial energetics and barrier integrity through extracellular mitochondrial transfer [19]. Herein, we first investigated the protein content of EVs that are spontaneously released by NSCs.…”
Section: Discussionmentioning
confidence: 99%